Tire aging: A state-of-the-art review - Pietro Stabile; Gianpiero Mastinu; Massimiliano Gobbi; Perla Bardini (Engineering Science and Technology, an International Journal)
Tire aging is a complex process driven by several environmental and mechanical factors. It significantly impacts vehicle safety and performance, presenting a critical challenge for engineers material scientists. This review paper presents a comprehensive analysis of the key factors affecting the aging of tires (namely oxidation, thermal degradation, ultraviolet (UV) radiation, ozone concentration, and humidity) and examines how each contributes to the loss of mechanical integrity in rubber compounds. Quantitative analyses from the literature show, for instance, that prolonged aging of rubber compounds mainly reduces elongation at break and tensile strength, while modulus and hardness increase. On the tire, these changes lead to an increased risk of failure, reduced traction capabilities, handling issues. For each aging factor, the specific aging mechanism is explored. The review further examines the primary experimental methods used to study the tire aging phenomenon. Particular emphasis is placed on the use of accelerated aging tests and climate chambers. While most studies rely on simplified material specimens, this review highlights the need for methods that better replicate real operational conditions. The paper also addresses the complex synergistic effects arising from the simultaneous action of multiple aging factors, an area that is largely underexplored in the current literature. A major challenge is the definition of accelerated aging test procedures, especially for tires, which involve the combination of mechanical loading and environmental factors. This review bridges fundamental theory of tire aging with practical engineering applications, setting the groundwork for future research in this field.